Behavior management in dentistry for children - Wright, Gerald Z.; Kupietzky, Ari; Wright, Gerald Z. (Ames, Iowa : John Wiley & Sons Inc., 2014)
Guiding patient behavior is as important as ever for the practicing dentist, and the behavior of pediatric patients is perhaps the most challenging to manage. Drs. Wright and Kupietzky here update Dr. Wright's classic work on managing pediatric dental patients. Behavior Management in Dentistry for Children,2nd Edition, has been entirely rewritten and includes the latest and most effective management strategies from an international team of experts in the field. The book addresses the influence of family and parenting styles on children's behavior and the.
Understanding key moments in child development / Eileen Wood -- Children's behavior in the dental office / J.S.J. Veerkamp, Gerald Z. Wright -- Influence of the family / Barbara Sheller -- Establishing a dental home / Anna B. Fuks, Ari Kupietzky -- Non-pharmacologic approaches in behavior management / Gerald Z. Wright, Ari Kupietzky -- Children with disabilities / Gunilla Klingberg -- Local anesthesia / Steven Schwartz, Ari Kupietzky -- Introduction to pharmacological techniques : a historical perspective / G.Z. Wright, Ari Kupietzky -- Sedation for the pediatric patient / Stephen Wilson -- Nitrous oxide/oxygen inhalation sedation in children / Dimitris Emmanouil, Ari Kupietzky -- Minimal and moderate sedation agents / Stephen Wilson -- Working with a dentist anesthesiologist / Kenneth Reed, Amanda Okundaye -- The use of general anesthesia in behavior management / Marcio A. da Fonseca, Travis Nelson -- Management of emergencies associated with pediatric dental sedation / Kenneth Reed, Amanda Okundaye -- Practical considerations and the dental team / Jonathon E. Lee, Brian D. Lee -- The dental office / Jonathon E. Lee, Brian D. Lee, Gerald Z. Wright, Ari Kupietzky.
Preceded by Behavior management in dentistry for children / by Gerald Z. Wright. 1975.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Pedodontics; Child psychology; Behavior Control -- methods; Dental Care for Children -- methods; Adolescent; Anesthesia, Dental -- methods; Child behavior; Child; Dentist-Patient Relations; Infant; Electronic books